Cytokine signaling converging on IL11 in ILD fibroblasts provokes aberrant epithelial differentiation signatures - Kastlmeier, Miriam T.; Gonzalez-Rodriguez, Erika; Cabanis, Phoebe; Guenther, Eva M.; König, Ann-Christine; Han, Lianyong; Hauck, Stefanie M.; See, Fenja; Asgharpour, Sara; Bukas, Christina; Burgstaller, Gerald; Piraud, Marie; et al. (Frontiers in Immunology, 2023)
Introduction Interstitial lung disease (ILD) is a heterogenous group of lung disorders where destruction and incomplete regeneration of the lung parenchyma often results in persistent architectural distortion of the pulmonary scaffold. Continuous mesenchyme-centered, disease-relevant signaling likely initiates and perpetuates the fibrotic remodeling process, specifically targeting the epithelial cell compartment, thereby destroying the gas exchange area. Methods With the aim of identifying functional mediators of the lung mesenchymal-epithelial crosstalk with potential as new targets for therapeutic strategies, we developed a 3D organoid co-culture model based on human induced pluripotent stem cell-derived alveolar epithelial type 2 cells that form alveolar organoids in presence of lung fibroblasts from fibrotic-ILD patients, in our study referring to cases of pulmonary fibrosis, as well as control cell line (IMR-90). Results While organoid formation capacity and size was comparable in the presence of fibrotic-ILD or control lung fibroblasts, metabolic activity was significantly increased in fibrotic-ILD co-cultures. Alveolar organoids cultured with fibrotic-ILD fibroblasts further demonstrated reduced stem cell function as reflected by reduced Surfactant Protein C gene expression together with an aberrant basaloid-prone differentiation program indicated by elevated Cadherin 2, Bone Morphogenic Protein 4 and Vimentin transcription. To screen for key mediators of the misguided mesenchymal-to-epithelial crosstalk with a focus on disease-relevant inflammatory processes, we used mass spectrometry and characterized the secretome of end stage fibrotic-ILD lung fibroblasts in comparison to non-chronic lung disease (CLD) patient fibroblasts. Out of the over 2000 proteins detected by this experimental approach, 47 proteins were differentially abundant comparing fibrotic-ILD and non-CLD fibroblast secretome. The fibrotic-ILD secretome profile was dominated by chemokines, including CXCL1, CXCL3, and CXCL8, interfering with growth factor signaling orchestrated by Interleukin 11 (IL11), steering fibrogenic cell-cell communication, and proteins regulating extracellular matrix remodeling including epithelial-to-mesenchymal transition. When in turn treating alveolar organoids with IL11, we recapitulated the co-culture results obtained with primary fibrotic-ILD fibroblasts including changes in metabolic activity. Conclusion We identified mediators likely contributing to the disease-perpetuating mesenchymal-to-epithelial crosstalk in ILD. In our alveolar organoid co-cultures, we were able to highlight the importance of fibroblast-initiated aberrant epithelial differentiation and confirmed IL11 as a key player in fibrotic-ILD pathogenesis by unbiased fibroblast secretome analysis.